2019
DOI: 10.1002/ieam.4188
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Land‐use and Land‐cover Dynamics of Adama District, Ethiopia and Its Implication to Greenhouse Gas Emissions

Abstract: Uncontrolled change in land use and land cover (LULC) enhances the concentrations of greenhouse gases in the atmosphere. This study, therefore, is aimed at the spatiotemporal analysis of LULC dynamics and their implications for the greenhouse gas emissions of the Adama district of Ethiopia. The dry season Landsat image Thematic Mapper (TM) of 1986, Enhanced Thematic Mapper (ETM) of 2000, and Enhanced Thematic Mapper Plus (ETM+) of 2014 were downloaded from the United States Geological Survey Global Visualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…The shift of wetland to other land use types like agricultural and bush encroached areas results water scarcity on the grazing area and currently this is one of the major problems in the study area, that caused for the decline of the livestock number [16]. The transition matrices of LULC showed that major change was observed in grassland, wetland and forestland area and mainly transformed to agricultural land, bare land and shrub land LULC types (Table 2) from 2019 year, which is similar to the findings of [39]. As shown in (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The shift of wetland to other land use types like agricultural and bush encroached areas results water scarcity on the grazing area and currently this is one of the major problems in the study area, that caused for the decline of the livestock number [16]. The transition matrices of LULC showed that major change was observed in grassland, wetland and forestland area and mainly transformed to agricultural land, bare land and shrub land LULC types (Table 2) from 2019 year, which is similar to the findings of [39]. As shown in (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The shift of wetland to other land use types like agricultural and bush encroached areas results water scarcity on the grazing area and currently this is one of the major problems in the study area, that caused for the decline of the livestock number [16]. The transition matrices of LULC showed that major change was observed in grassland, wetland and forestland area and mainly transformed to agricultural land, bare land and shrub land LULC types (Table 2) from 2019 year, which is similar to the ndings of [39]. As shown in (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…This indicates that only 64.2% of grassland, 52.1% of wetland, 90.2% of forestland, 97.2% of bare land, 98.1% of agricultural land and 99.8% of shrub land remained within the same LULC types in 2019. The major change was observed in grassland, wetland and forestland area and mainly transformed to agricultural land, bare land and shrub land LULC types (Table 4 from 2019 year), which is similar to the findings of [44]. As shown in Fig.…”
Section: Land Use and Land Cover Change Transition Matrix From 1992-2019supporting
confidence: 84%